Onset of Possible Octupole Deformation in Rotational 106,108Te Nuclei - Wang, Hua-Lei; Liu, Hong-Liang; Xu, Fu-Rong; Jiao, Chang-Feng (Progress of Theoretical Physics, 2012)
Octupole correlation in near-proton-drip-line nuclei 106,108Te has been investigated using improved total Routhian surface calculations with the inclusion of reflection-asymmetric deformations. It is found that 106,108Te have reflection-symmetric shapes at low spins, then become octupole deformed at rotational frequencies ¶ÿ°÷0.50 - 0.60 MeV/\hbar. The onset of strong octupole correlation is consistent with the observation of octupole bands in 108Te. The octupole structure predicted for 106Te would be accessible in experiments.